Financial costs of urban sprawl : a case study of housing development in Penang State / Shahriza Osman - Osman, Shahriza (Institute of Graduate Studies, 2017)
Penang State experienced rapid urban development for the past three decades. Urban sprawl is a global phenomenon and is characterised by increase in population growth in urban areas, migration, change in built-up areas and spatial form. Urban sprawl creates economic, social and environmental costs such as environmental degradation due to more intensive land and car use as well as economic challenges brought about by increased distance to jobs, goods and service markets. Infrastructure costs seem to increase in new sprawling development than compact development. It becoming more difficult to pay for the additional costs incurred by urban sprawl.